Spatial distribution and nesting habits of nannotrigona mellaria (APIDAE: MELIPONINI) in one locality of Cali (Colombia) - Martínez López, Sergio; Soto Medina, Edier Alberto; Sandoval Arango, Stephania; Otero Ospina, Joel Tupac (Instituto de Ecología, A.C., 2017)
ABSTRACT. Meliponini bees are important pollinators in naturalhabitats and their distribution may be affected differently by humans, the buildings causing changes in micro-climate and vegetation structure and composition, which may affects stingless bee communities. However, there is much to know about their behavior in these conditions. The aim of this study was to describe nesting habits of Nannotrigona mellaria at an urban environment. Sampling was conducted at the Universidad del Valle, Melendez campus, the nest location and number of colonies per site, were recorded and mapped using the program DIVA-GIS. The nest distribution was analyzed with a non-spatial analysis performed by adjusting the data to the negative binomial distribution with a Chi2 test. Additionally, Spatial Analysis by Distance Indices (SADIE) was performed. We found 242 nest, of which 130 were on Pithecellobium dulce (Fabaceae: Faboideae), and 91 where found in buildings. Analyses suggested that Nannotrigona mellaria nests have an aggregated distribution at the Universidad del Valle, this probably due to factors such as the location and abundance of resources, usable spaces for nesting and limitations as to the maximum flight because the size of the bees. In addition, P. dulce was mainly used to establish colonies, however, it is clear that buildings are an important space resource for this species and provide the necessary conditions for the establishment of colonies in an  urban habitat.